2018
DOI: 10.1155/2018/2012078
|View full text |Cite
|
Sign up to set email alerts
|

PATRI, a Genomics Data Integration Tool for Biomarker Discovery

Abstract: The availability of genomic datasets in association with clinical, phenotypic, and drug sensitivity information represents an invaluable source for potential therapeutic applications, supporting the identification of new drug sensitivity biomarkers and pharmacological targets. Drug discovery and precision oncology can largely benefit from the integration of treatment molecular discriminants obtained from cell line models and clinical tumor samples; however this task demands comprehensive analysis approaches fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Thus, the development of an analysis environment that exploits both canonical pathways and new extended network interactions may improve our understanding of the significance of highly regulated DEGs within the context of liver pathological processes (Cerami et al, 2010; Khatri et al, 2012). There has been tremendous progress in the pathway curation and integration process during the past few years and that progress has resulted in novel pathway tools (Fabregat et al, 2017; Huang et al, 2017; Uppal et al, 2017; Wang et al, 2017; Forsberg et al, 2018; Pittman et al, 2018; Ukmar et al, 2018). However, these tools are still highly fragmented and not integrated into a single framework for optimal DEGs analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of an analysis environment that exploits both canonical pathways and new extended network interactions may improve our understanding of the significance of highly regulated DEGs within the context of liver pathological processes (Cerami et al, 2010; Khatri et al, 2012). There has been tremendous progress in the pathway curation and integration process during the past few years and that progress has resulted in novel pathway tools (Fabregat et al, 2017; Huang et al, 2017; Uppal et al, 2017; Wang et al, 2017; Forsberg et al, 2018; Pittman et al, 2018; Ukmar et al, 2018). However, these tools are still highly fragmented and not integrated into a single framework for optimal DEGs analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of HMGB2, an interacting partner MIEN1 sensitizes head and neck squamous cell carcinoma against cisplatin and 5-fluorouracil [ 130 ] . MIEN1 showed increased expression in lapatinib-sensitive breast cancer cells compared to lapatinib-resistant breast cancer cells [ 131 ] . Colony growth in soft agar, invasion into collagen matrix and formation of large acinar structures in three-dimensional cell cultures experiment demonstrated that increased MIEN1 expression is highly associated with cell transformation including epithelial to mesenchymal transition and reduced expression of E-cadherin and keratin-8 [ 132 ] .…”
Section: Novel Targets In Drug Resistancementioning
confidence: 99%
“…Precision medicine strongly relies on research models 13,14 and cancer cell lines can represent widely accessible tools for the investigation and the functional characterization of therapeutically actionable KGF targets, paralleling the genetic alterations present in primary tumor samples 11,[15][16][17][18][19] . Extensive KGF molecular annotation would therefore greatly support the drug development pipeline and aid the parallel advancement of companion diagnostic tools for the assessment of patient treatment eligibility, such as multiplex amplicon approaches 20 or Anchored Multiplex PCR (AMP) 21 .…”
Section: Introductionmentioning
confidence: 99%